2020
DOI: 10.3389/fcvm.2020.585268
|View full text |Cite
|
Sign up to set email alerts
|

Association Between GJA1 rs13216675 T>C Polymorphism and Risk of Atrial Fibrillation: A Systematic Review and Meta-Analysis

Abstract: Background: Rs13216675 T>C polymorphism, an SNP (single-nucleotide polymorphism) close to the gap junction protein alpha 1 (GJA1) gene, has been reported to be associated with risk of atrial fibrillation (AF); however, the results remained inconclusive. We aimed to perform a systematic review to clarify the relationship between rs13216675 and risk of AF. Materials and methods: We systematically searched the databases of PubMed, EMBASE, Web of Science, and the Chinese National Knowledge Infrastructure up to Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A well-established AF locus, chromosome 6q22.31, houses the GJA1 gene [ 44 ]. Recent studies suggested that the single-nucleotide polymorphism (SNP) rs13216675, situated near the GJA1 gene on chromosome 6q22, was significantly associated with the risk of AF [ 45 ]. The GJA1 gene may be associated with abnormal atrial automaticity and involved in both the onset and persistence of AF [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A well-established AF locus, chromosome 6q22.31, houses the GJA1 gene [ 44 ]. Recent studies suggested that the single-nucleotide polymorphism (SNP) rs13216675, situated near the GJA1 gene on chromosome 6q22, was significantly associated with the risk of AF [ 45 ]. The GJA1 gene may be associated with abnormal atrial automaticity and involved in both the onset and persistence of AF [ 46 ].…”
Section: Discussionmentioning
confidence: 99%